Access to Finance for Youth SMEs in Rwanda: A Look at Youth SME Financing Impediments from a Policy Perspective - Dushimimana M. A; Dixit A.; Sinining V (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2020)
In many developing countries and developed countries alike, small and medium enterprises (SMEs) are the lead drivers of job creation and economic development. This review paper explores access to finance for youth-led Small and Medium Enterprises (SMEs), analyses youth SME financing impediments from a policy perspective and concludes with a consolidated view and relevant recommendations to enable youth in developing countries like Rwanda to build thriving businesses.